2005
DOI: 10.2131/jts.30.7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Maternal Exposure to a Low Dose of Diethylstilbestrol on Sexual Dimorphic Nucleus Volume and Male Reproductive System in Rat Offspring

Abstract: -Diethylstilbestrol (DES) was administered subcutaneously at 0.5, 1.5 or 4.5 µg/kg/day (DES 0.5, 1.5 and 4.5 groups, respectively) to pregnant SD rats daily on days 7-21 of gestation, to investigate its effects on the development and functions of the reproductive system in their male offspring. Of the 10 pregnant rats in the DES 4.5 group, only 1 delivered, and this rat could not suckle the pups. Rat pups in the DES 0.5 and 1.5 groups were autopsied at 1, 3, 6 and 15 weeks after birth. The testosterone concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…In our previous studies [5,27], we determined the effects of various levels of DES (15, 4.5, 1.5 and 0.5 μg/kg/day) considering Boylan's results [30], achieved by administering various doses of DES s.c. to SD rats, showing that 1.5 μg/kg/day is approximately the maximum possible dose. In the present study, the testis/body weight ratio was lower in the DES 0.5 group than in the control group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous studies [5,27], we determined the effects of various levels of DES (15, 4.5, 1.5 and 0.5 μg/kg/day) considering Boylan's results [30], achieved by administering various doses of DES s.c. to SD rats, showing that 1.5 μg/kg/day is approximately the maximum possible dose. In the present study, the testis/body weight ratio was lower in the DES 0.5 group than in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study [27], DES administration disrupted the spermatogenic cycle at 15 weeks after birth in comparison with 6 weeks of gestation, but only five 15-week-old pups were used to examine spermatogenesis, although ten 6-week-old pups were employed in other analyses. Hess et al [42] employed the testes of 10 pups and demonstrated that classification of more than 200 seminiferous tubules per pup provided sufficiently reliable data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ikeda et al [80] showed that prenatal dioxin exposure decreased SDN-POA volume of male rats but did not influence this parameter in female rats, suggesting a demasculinizing effect. The estrogenic pharmaceutical diethylstilbestrol (DES) also organizes the developing hypothalamus: the SDN-POA region was increased in size in the female rat but was not affected in male littermates, indicating a masculinizing effect [169]. Prenatal ethinyl estradiol, the most common estrogen in oral steroid contraceptives, decreased SDN-POA volume of males but had no effect in females, suggesting a demasculinizing effect [141].…”
Section: Effects Of Perinatal Edcs On the Avpv And Sdn-poa Morphologymentioning
confidence: 99%